Volume 3: Heat Transfer; Electric Power; Industrial and Cogeneration 1999
DOI: 10.1115/99-gt-162
|View full text |Cite
|
Sign up to set email alerts
|

Film Cooling Effectiveness Predictions for Short Holes Fed by a Narrow Plenum

Abstract: This study evaluates the ability of available turbulence models in the commercial software FLUENT to predict film cooling effectiveness for a single row of short (LID = 2.91) . film cooling holes fed by a narrow plenum (H /D = 1). The results are compared to experimental data obtained by the present investigators. The study concentrates on the near-hole region for the geometry being studied experimentally by the present investigators. The results of the study indicate that the use of wall functions to predict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Numerical simulations (Hale, 1998) provide confirmation of the existence of this vortex pair. Using FLUENT v.4 on an IBM RS 6000 with 512 MB of RAM, the plenum flow (H/D = 0.66), flow within the injection hole (a = 90°, UD = 0.66), and the crossflow were modeled.…”
Section: Flow Visualization and Numerical Simulationmentioning
confidence: 72%
See 1 more Smart Citation
“…Numerical simulations (Hale, 1998) provide confirmation of the existence of this vortex pair. Using FLUENT v.4 on an IBM RS 6000 with 512 MB of RAM, the plenum flow (H/D = 0.66), flow within the injection hole (a = 90°, UD = 0.66), and the crossflow were modeled.…”
Section: Flow Visualization and Numerical Simulationmentioning
confidence: 72%
“…Studies have also been reported by Leylek (1996, 1997) and Ferguson et at (1998), who emphasize the importance of properly modeling the flow physics by including the plenum and injection hole within the computational domain. Hale et at (1999), in a companion computational study, evaluated various turbulence models for their ability to predict adiabatic effectiveness for the same configurations reported here.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The criteria for convergence of the conservation equations were a reduction in the residuals by more than four orders of magnitude for each equation, and an imbalance in the mass flow rate at the film hole exit plane inferior to 10 2 5 . Film cooling scheme for gas turbines Hale et al (1999) evaluated several different turbulence models and wall function treatments available in the commercial CFD code FLUENT, assessing the ability of these combined models to predict the film cooling effectiveness for streamwise blowing from short injection holes (with L/D h ¼ 2.91, b ¼ 08 and a ¼ 358 in the present notation) fed by a narrow plenum. The results of their study indicated that the use of usual wall functions to predict film cooling effectiveness in the near-hole region is problematic due to apparent boundary layer separation in that region.…”
Section: Mathematical Modeling and Boundary Conditionsmentioning
confidence: 99%
“…The small separation region downstream of the blowing holes that Hale et al 21 identify in their streamwise blowing case will be signi cantly altered for the present compound angle blowing. Because it is known that the structure within square jets is likely to be more complex than that in round jets and that the separation will be very different for the compound blowing orientation, it was thoughtthat simple engineeringmodels of turbulencemight perform better in predictions of compound injection with round holes than with square.…”
Section: Numerical Methods and Comparisons With Measured Resultsmentioning
confidence: 93%
“…Nevertheless, their numerical predictionsshow that the ow near the jet exit is grossly oscillatory, with effective Strouhal numbers of about 0.4, based on jet velocity and size. Modest agreement is obtained in comparisons with the detailed measurements of mean quantities reported by Ajersch et al 15 Hale et al 21 evaluated several different turbulence models and wall function treatments available in the commercial computational uid dynamics code FLUENT, assessing the ability of these combined models to predictthe lm coolingeffectivenessfor streamwise blowing from short injectionholes (with L=d D 2:91,¯D 0 deg, and ® D 35 deg in the present notation) fed by a narrow plenum. The results of their study indicated that the use of usual wall functions to predict lm cooling effectivenessin the near-holeregionis problematic due to apparent boundary-layer separation in that region.…”
Section: Numerical Methods and Comparisons With Measured Resultsmentioning
confidence: 97%